A literature review of the evolution of British prefabricated low-rise housing. Issue 2 (9th May 2016) - O'Neill, Daniel; Organ, Samantha
Abstract : Purpose: – The purpose of this paper is to explore academic papers and reports and present a chronology of the evolution of British low-rise prefabricated housing. The paper provides chronological information for construction and surveying researchers undertaking research in associated areas. Design/methodology/approach: – This is a qualitative literature review, providing an exploration and analysis of academic papers and reports on low-rise prefabricated housing. Findings: – A substantial literature was discovered. However, there are gaps in the available literature. The history of British construction technology is a rich research area but is under-researched. Prefabricated housing has a long history dating back to the eleventh century. Stigmatised from the failures of housing in the twentieth century, it is being increasingly used again in the twenty-first century when considering mass housing supply. Research limitations/implications: – This paper provides researchers with an overview of the history of low-rise prefabricated housing in Britain. It is not a comprehensive in-depth study; such would require numerous larger individual studies. Originality/value: – From reviewing literature it was evident that there was a broad literature, but there was no single journal publication exploring the evolution of British low-rise prefabricated housing. The research provides an overview, exploration and analysis of the literature while providing a chronology. The evolution of prefabricated housing is chronologically presented. Areas for further research are also recommended.